2018
DOI: 10.1097/hmr.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between organizational and individual support, nurses’ ethical competence, ethical safety, and work satisfaction

Abstract: These findings should assist nurse leaders to implement effective support practices to strengthen nurses' ethical competence, ethical safety, and work satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
2
28
0
4
Order By: Relevance
“…This is supported by previous findings (Jackson et al., ). Other studies also suggest whistleblowing requiring moral courage (Numminen, Repo, & Leino‐Kilpi, ) and ethical sensitivity, (Poikkeus, Suhonen, Katajisto, & Leino‐Kilpi, ) to act when wrongdoing and ethical problems are observed. In contrast, findings about individual characteristics not contributing to whistleblowing were presented by Alinaghian, Isfahani, and Safari ().…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by previous findings (Jackson et al., ). Other studies also suggest whistleblowing requiring moral courage (Numminen, Repo, & Leino‐Kilpi, ) and ethical sensitivity, (Poikkeus, Suhonen, Katajisto, & Leino‐Kilpi, ) to act when wrongdoing and ethical problems are observed. In contrast, findings about individual characteristics not contributing to whistleblowing were presented by Alinaghian, Isfahani, and Safari ().…”
Section: Discussionmentioning
confidence: 96%
“…As is the case with learning professional techniques, nurses' moral performance is affected by their work environment. To examine why these changes happen, we searched the relevant literature, and we found that changes in moral competencies were the topic of several studies [ 14 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is the case with learning professional techniques, nurses' moral performance is affected by their work environment. In order to examine why these changes happen, we searched the relevant literature, and we found that changes in moral competencies were the topic of several studies (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%